DETERMINAN PROFITABILITAS DAN IMPLIKASINYA TERHADAP NILAI PERUSAHAAN DENGAN LEVERAGE SEBAGAI VARIABEL INTERVENING - Dede Alfiana; Wawan Ichwanudin; Enis Khaerunnisa (Politeknik Negeri Ambon, 2023)
This research was conducted with the aim of knowing the ability of leverage to mediate the implications of profitability on firm value, with sales growth and cash turnover as determinants of profitability. The population in this study are companies from the trade, service and investment sectors in the tourism sub-sector, restaurants and hotels listed on the Indonesia Stock Exchange (IDX) for the period 2016 to 2020 with a total population of 19 companies. The antecedent variable of company growth is proxied by sales growth and the activity ratio is proxied by Cash Turnover, the independent variable of profitability is measured using ROE (Return on Equity), the dependent variable of company value is proxied by PBV (Price Book Value), and the intervening variable Leverage is proxied by DER (Debt to Equity Ratio). This study uses secondary data obtained from ICMD (Indonesian Capital Market Directory) for 2016-2020. Testing was carried out using SPSS. The results showed that sales growth has a positive effect on profitability, cash turnover has a positive effect on profitability, profitability has a positive effect on leverage, leverage has a positive effect on firm value, profitability has a negative effect on firm value, leverage mediates profitability on firm value..